Inhibitory mechanism of influence of thyroid hormones on cognitive function of the brain. - A. G. Rodynsky; E. M. Demchenko; E. J. Kondratieva; A. J. Golubka; D. S. Yaroshenko (Medičnì Perspektivi)
In experiments on young rats there were studied changes in the fatty acid spectrum of fraction of  free fatty acids (FFA) of neocortex and hippocampus in conditions of thyroid dysfunction. Elevated levels of thyroid hormones caused accumulation of polyunsaturated linoleic and linolenic acids in the neocortex by 2 times, in the hippocampus – by 52%. State of hypothyroidism also contributed to the increase of C18: 2,3 in the neocortex by 74.4%. Growth of share of unsaturated fatty acid fraction in the content of fatty acid spectrum of neocortex also was accompanied by decrease in saturated C16:0 and C21:0 by 25% and 36% respectively. Increase of the level of unsaturated fatty acids fraction of the cerebral cortex is possibly associated with the decrease in "unsaturation" structure of lipids, which in its turn may enhance serotonergic synaptic activity. Research of concentration of neuromediator amino acids in neocortex showed increase of serotonin content both in conditions of hyperthyroidism and hypothyroidism. In conditions of hyperthyroidism increased content of GABA was observed. Activity of serotonin- and GABA- ergic neurotransmitter systems of the brain in conditions of hyperthyroidism can be considered as increase of inhibitory processes in the  effect of feedback. In conditions of experimental hypothyroidism activation of the inhibitory effects of CNS serotonergic system may be one of the ways to reduce the metabolism.